Antiproliferative Properties of Papaver rhoeas Ovule Extracts and Derived Fractions Tested on HL60 Leukemia Human Cells - Elisa Ovidi; Valentina Laghezza Masci; Stefania Garzoli; Gabriella Gambellini; Saran Vittoria Keita; Daniele Zago; Giovanni Turchetti; Lorenzo Modesti; Antonio Tiezzi (Molecules, 2020)
Papaver rhoeas plant is common in many regions worldwide and contributes to the landscape with its red flower. In the present study we first carried out morphological investigation by optical and scanning electron microscopy of the ovules within the ovary. After ovules’ isolation we prepared extracts to test possible cytotoxic activities on HL60 leukemia human cells and investigated the extracts using thin-layer chromatography (TLC) and gas-chromatography/mass spectrometry (GC-MS). P. rhoeas ovules showed an elongated, round shape and the presence of ordered sculptures on the ovule surface. The ovule extracts showed cytotoxic activity on HL60 human cells mainly found in some TLC-isolated spots. Compounds consisting of active spots were identified by GC-MS investigations. Our findings on the P. rhoeas ovule compounds open perspectives for further investigations of TLC-isolated spots on other human cancer cell lines.